Effect of Moringa oleifera on Atherogenic Lipoprotein Indices of HIV Infected Adults on Tenofovir-Based Antiretroviral Regimen in UPTH, Nigeria - Anyanwu, C. F.; Owhonda, G. C.; Obianime, A. W.; Siminialayi, I. M.; Kanee, R. B.; Jr., E. O. Aigbogun (Challenges and Advances in Pharmaceutical Research Vol. 5, 2022)
The administration of Tenofovir (TDF) based (Tenofovir/Lamivudine/Efavirenz) antiretroviral regimen for the management of HIV has been associated with dyslipidaemia, which are associated cardiovascular-related complications, and reduced life expectancy. Through a randomised comparative trial, the study evaluated the effect of Moringa oleifera supplementation on metabolic abnormalities associated with HIV patients on TDF-based regimen. The RCT was a time dependent study that comprised of two arms (intervention TDF-M and control TDF-NM). Of the 140 recruited participants 56 were in the TDF-M group (administered Moringa Supplement) and 84 in the TDF-NM (control). At baseline, more than half of the patients showed aberrant atherogenic lipoprotein indices (Log [TC/HDL-C] = 85.7%; TC/HDL-C = 58.5% and LDL-C/HDL-C = 51.4%); albeit at lower levels. The prevalence of TDF-M participants at risk of CVD had reduced to 20% after 12 weeks of Moringa supplement administration, showing a remarkable (40.4 percent) decline, while the prevalence of TDF-NM subject at risk of CVD rose to 53.6% (x2=26.67, P<0.001). HIV patients on a TDF-based regimen who were at risk of CVD exhibited higher TGL and LDL levels, which had an inverse effect on HDL levels and a negative effect on atherogenic indices. The changes in proportion of TDF-M group were not significantly different from TDF-NM group after 4 weeks (visit 1); however, after 12 weeks (visit 2) of moringa administration, the subjects on Moringa had 4.67 [2.39 – 9.13] higher odds of normal API (x2[Yates]=24.688; P<0.001), 2.39 [1.58 – 3.60] higher odds of normal TC/HDL-c (x2[Yates]=16.879; P<0.001), and 2.09 [1.56 – 2.80] higher odds of normal LDL/HDL-c (x2[Yates]=23.388; P<0.001). The study observed marked changes in the atherogenic lipoprotein indices of both groups, with better indices for the TDF-NM group. This, therefore strengthens the advocacy for the inclusion of Moringa as dietary supplement for management of ART induced dyslipidaemia.